Role of guard-cell ABA in determining steady-state stomatal aperture and prompt vapor-pressure-deficit response. (April 2019) - Yaaran, Adi; Negin, Boaz; Moshelion, Menachem
Graphical abstract: Highlights: ABA plays a minor role in stomatal response to rapid increase in VPD. ABA restricts stomatal apertures under well-irrigated conditions. ABA-insensitive guard cells affect stomatal proliferation. Abstract: Abscisic acid (ABA) is known to be involved in stomatal closure. However, its role in stomatal response to rapid increases in the vapor pressure deficit (VPD) is unclear. To study this issue, we generated guard cell-specific ABA-insensitive Arabidopsis plants (guard-cell specific abi1-1 ; GCabi). Under non-stressed conditions, the stomatal conductance (gs ) and apertures of GCabi plants were greater than those of control plants. This supports guard-cell ABA role as limiting steady-state stomatal aperture under non-stressful conditions. When there was a rapid increase in VPD (0.15 to 1 kPa), the gs and stomatal apertures of GCabi decreased in a manner similar that observed in the WT control, but different from that observed in WT plants treated with fusicoccin. Low VPD increased the size of the stomatal apertures of the WT, but not of GCabi. We conclude that guard-cell ABA does not play a significant role in the initial, rapid stomatal closure that occurs in response to an increase in VPD, but is important for stomatal adaptation to ambient VPD. We propose a biphasic angiosperm VPD-sensing model that includes an initial ABA-independent phase and a subsequent ABA-dependent steady-state phase in which stomatal behavior is optimized for ambient VPD conditions.